Escaping the Middle Innovation Trap: Case Studies of Two Successful Spin-off Companies from a Malaysian Research University - Shamsir, Mohd Shahir; Abd Jamil, Azlin (Journal of Research Management and Governance, 2019)
The concept of the "middle innovation trap" has been proposed as a phenomenon of a â€œfailed transformation from implementation based to concept design based capabilityâ€ (Lee et al., 2019). It has trapped nations from evolving from middle income to high-income status. Over the past two decades, many countries have been caught in the middle-income traps. The same phenomenon can possibly be observed in institutions of higher learning, especially government-funded institutions that are a microcosm of the country as their development and wellbeing are intricately linked to the country’s finances. Institutions are often well funded with significant capital expenditure during their inception, enabling them to possess the latest technologies with good teaching and research capabilities which in turn could stagnant and degrade if the government switches to fund other inception projects. Hence, these institutions are left to fend on their own, creating a technological and innovation trap that is insurmountable without repeated investment effort to bridge the gap created by rapidly advancing technologies or narrowing of the long tail of scientific research. The presence of a â€œmiddle innovationâ€ trap in a university may hinder the successful commercialisation of its innovation. In this study, two cases from Universiti Teknologi Malaysia (UTM) are described; robotics and skin-care innovation that has been successfully commercialised, hence â€œescapedâ€ the middle innovation trap. In both cases, the commercialised innovation was very dependent on the inventors. These are self-driven extraordinary individuals who developed extensive industrial insights acquired by additional training not accessible to their peers. Their products are not novel and utilise existing technologies that are shaped into commercially available products or services. Although UTM technology transfer office is known for its support and flexibility towards academics pursuing commercialisation, the role of the extraordinary individuals who possess exceptional drive is the key factor in escaping the trap. In conclusion, escaping from the middle innovation trap would only be successful by providing significant and continuous support to the correct type of academic staff. Therefore, the selection of the correct people is more important than the product being offered.